ANALISIS PENGARUH MOTIVASI INTRINSIK TERHADAP KEPUASAN KERJA YANG BERDAMPAK PADA KINERJA KARYAWAN DI PT. JHONS GF SEMARANG - Bambang Guritno; Heri Prabowo (BBM (Buletin Bisnis & Manajemen), 2016)
This research analyzes many factors which influence of the employees working. The pupose of the research is fainding many factors which influence the employee working. The contents is intrinsic motivation and satisfied of working releated with the influence the employee working. The object of this research is employees of PT. Jhons GF.Purposive sampling which choisen is to find out the data which needed in this studies there are 85 responden and all of the are PT. Jhons GF employee. The data analysis used SPSS program 19 series. Before doing regreesion analysis, the process analysis is trought many steps whisvh one of the is validity analysis, reiability test and classic assumtion test.In this research has three hypothesis and depards of the research analysis show tht three hypothesis are acepted, it means the conclution of this research intrinsic motivation it influence satisfied of working towards increasing of employees working. Kata Kunci : intrinsic motivation, satisfied of working and employees working